2021
DOI: 10.1177/0300060521993974
|View full text |Cite
|
Sign up to set email alerts
|

Chemical meningitis after cervical transforaminal epidural steroid injection: a case report

Abstract: We herein report a case of chemical meningitis that developed after cervical transforaminal steroid injection. A 49-year-old man presented with symptoms of meningitis (severe headache and neck stiffness) after cervical transforaminal steroid injection at the right C5–6 level. The injection solution was a mixture of lidocaine (0.3 mL), hyaluronidase (1 mL), placenta hydrolysate (2 mL), and normal saline (1 mL). The patient developed symptoms of meningitis 2.5 hours after the cervical epidural injection. Cerebro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…injection with a mixture of lidocaine, hyaluronidase, placenta hydrolysate, and normal saline. 9 In this patient, it was difficult to delineate the cause of the condition using only the initial CSF analysis, without culture. However, due to the rapid onset of symptoms after the procedure, about 2.5 h, the patient was symptomatically treated with analgesics and fluid management with the assumption of chemical meningitis and had rapid relief after 3 days.…”
Section: Discussionmentioning
confidence: 94%
“…injection with a mixture of lidocaine, hyaluronidase, placenta hydrolysate, and normal saline. 9 In this patient, it was difficult to delineate the cause of the condition using only the initial CSF analysis, without culture. However, due to the rapid onset of symptoms after the procedure, about 2.5 h, the patient was symptomatically treated with analgesics and fluid management with the assumption of chemical meningitis and had rapid relief after 3 days.…”
Section: Discussionmentioning
confidence: 94%
“…In our study, no serious complication was observed in either group, while one patient had severe headache. Acute chemical meningitis may rarely develop after ESI [32].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no serious complication was observed in either group, while one patient had severe headache. Acute chemical meningitis may rarely develop after ESI [29].…”
Section: Discussionmentioning
confidence: 99%